Kinetic evidence that echinomycin migrates between potential DNA binding sites. - Fox, K R (1985)
The hypothesis that echinomycin locates its preferred nucleotide sequences in DNA by a process of "shuffling" between potential binding sites has been tested. Immediately after reacting with calf thymus DNA the antibiotic is relatively weakly bound inasmuch as the complex dissociates quite rapidly when detergent is added. If the complex is allowed to equilibrate for various periods of time after mixing, an increasing proportion of the bound antibiotic dissociates slowly on addition of detergent. The kinetics of appearance of the slowly-dissociating form, and its dependence upon ionic strength, are fully consistent with the shuffling model. In contrast the dissociation profiles from poly(dG-dC) and poly(dA-dT) are independent of mixing time.